A COMPARISON OF DIRECT OBSERVATIONS OF VELOCITY AND TRANSPORT IN THE WINDWARD PASSAGE - Bulgakov S.N.; Bulgakov N.P.; Ivanov V.A. (My University, 2003)
Velocity and water transport through the Windward Passage is estimated from a review of prior investigations and a new analysis of mooring observations conducted on February, 18, 1965 and November, 19-23, 1970 in the former USSR. These may be the only available direct velocity measurements in this area. Direct current measurements indicate a transport of about 8 Sv ± 4 Sv into the Caribbean sea, which is consistent with values estimated by other authors. The transport figure based on November, 19- 23, 1970 data is interpreted as a surface outflow of 0.8 Sv in the upper 100 m, a mid-depth inflow of 10.7 Sv in the 100-700 m layer, and an outflow of 2.0 Sv below 700 m. The general current-countercurrent flow system of the upper 200 m in Windward Passage compares satisfactorily with recent ADCP observations in the Great Inagua Passage.
Keywords: Windward Passage; current measurements; data comparison